Effects of the rehabilitation process on somatometric indicators and the body composition of women with alimentary obesity. Osh - Abbas, Syed Ali; Kochkorbaevna, Kaipova Ajamal; G.V., Belov (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Obesity is often сonsider   as characteristics   of appearance, physical type  for someone attractive and  for someone not.With obesity, not only lipid metabolism suffers, general reaction of body decreases, the immune system, resistance to stress and psychological changes [ 2 ].Diagnosis of obesity, with all the obvious evidence is not easy, because there are no clear criteria for difference from the normal - an overweight is often not a sign of healthy or sick.Recently, computerized technologies and methods have appeared that make it possible to more accurately diagnose the extent of lipid metabolism disturbances and to evaluate the biological characters   of the revealed abnormalities [ 7, 11, 12 ].Restorative treatment of the metabolic syndrome should be complex and not instantaneous[ 3, 4, 5 ] .Although  the rapid weight reduction that is directed by  many programs offered at resorts and health centers .They often use hydrocolonal  therapy and various laxatives, for a week or ten days and the  patients loses 10-15 kg , but you can’t say it is  pathogenetic treatment.Metabolic and functional abnormalities are not corrected   and the  patients  gain weight quickly. [ 6, 10 ] .